2017
DOI: 10.2135/cropsci2016.06.0544
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a High‐Density Genetic Map and Its Application to QTL Identification for Fiber Strength in Upland Cotton

Abstract: Cotton (Gossypium sp.) is an important worldwide cash crop that provides a competitive renewable natural fiber supply for the demands of textile industry. The development of new textile technologies and the improvement of living standards increase the demands for both fiber quantity and fiber quality. ‘0–153’ is an upland cotton cultivar with excellent fiber quality derived from Asiatic cotton sources, especially with regards to fiber strength. To identify quantitative trait loci (QTLs) for fiber strength in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…But in the present study, a higher percentage of polymorphic SNP markers were mapped on D‐genome (799) than the A‐genome (631). This indicates that higher marker density is present on D‐genome than A‐genome, which is also evident in the map reported by Zhang et al (). In this study, we constructed the genetic map with 1,430 SNP markers spanning 3,149.8 cM.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…But in the present study, a higher percentage of polymorphic SNP markers were mapped on D‐genome (799) than the A‐genome (631). This indicates that higher marker density is present on D‐genome than A‐genome, which is also evident in the map reported by Zhang et al (). In this study, we constructed the genetic map with 1,430 SNP markers spanning 3,149.8 cM.…”
Section: Discussionsupporting
confidence: 78%
“…The large number of SNP markers detected in different cotton species (Byers, Harker, Yourstone, Maughan, & Udall, ; Van Deynze et al, ; Gore et al, ; Hulse‐Kemp, Ashrafi, et al, ; Hulse‐Kemp et al, ; Islam, Thyssen, Jenkins, & Fang, ; Lacape et al, ; Rai et al, ; Zhu, Spriggs, Taylor, Llewellyn, & Wilson, ) have helped the cotton researchers in genome‐based identification and mapping of QTL. Till now, only a few mapping studies in cotton have been based on SNP markers (Gore et al, ; Kumar et al, ; Li et al, ; Yu et al, ; Zhang et al, ). An international collaborative effort has developed the CottonSNP63k Illumina Infinium genotyping assay and genotyping these SNP markers in interspecific and intraspecific cotton F 2 populations (Hulse‐Kemp, Lemm, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-density genetic map constructed with single nucleotide polymorphisms (SNPs) based on CottonSNP70K chip (Zhang et al, 2017) and simple sequence repeats (SSRs; Sun et al, 2012) was used for the QTLs identification (Supplementary Table 1). The SNPs and SSRs were screened and excluded after several steps based on the following criteria: the SNPs that did not show three clearly defined clusters (AA, BB, and AB); second, the SNPs that their genotypes in one or both of the parents showed heterozygosis; third, the SNPs that had no polymorphism between parents; fourth, the SNPs and SSRs for which genotyping data were missing in more than 40% of the 196 RILs; and finally, the SNPs and SSRs with a significant segregation distortion ( P < 0.001).…”
Section: Methodsmentioning
confidence: 99%
“…The map spanned a total distance of 2,856.73 cM with 26 linkage groups, all of which were allocated into chromosomes of cotton genome, and an average marker interval of 1.20 cM. The quality criteria assessments of the genetic linkage map indicated that the segregation distortion of mapped markers was low (34.78% of the mapped markers showed distorted segregation) and that the collinearity of SNP and SSR markers between the genetic and physical maps had a sufficient consistency with their locations on both maps across the whole genome (Zhang et al, 2017). …”
Section: Methodsmentioning
confidence: 99%